2010
DOI: 10.1111/j.1365-2214.2010.01167.x
|View full text |Cite
|
Sign up to set email alerts
|

Governmental interventions and youth physical activity in France

Abstract: Data from a representative sample of 2474 French youth show that, despite a 7-year French Ministry of Health strategy for nutrition and physical activities, adolescents' motivation to practise sports and physical activities decreased significantly between 2001 and 2008. While this paper focuses on the context of physical activity in France, the general discussion may be applicable to other countries concerned with the obesity pandemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…), this ambitious programme does not seem to work in young people as it was intended to (Recours et al . ).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…), this ambitious programme does not seem to work in young people as it was intended to (Recours et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…For example, in France the launch by the French Ministry of Health of the French strategy for nutrition, PA and the prevention of obesity in 2002 (Hercberg ; Recours et al . ) appears as a milestone in the fight against physical inactivity and its related diseases. However, due to a number of political, cultural (Recours et al .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[4] Studies have shown that individuals' health information is effective on their behaviors. In other words, one of the essential elements for the prevention of non communicable diseases and the promotion of health is increasing the public knowledge concerning relevant issues[567] as well as the elimination of individuals' poverty of the awareness, related to health and prevention of non communicable diseases such as cancer. [8] Other research results suggest that awareness, beliefs and proper nutrition behaviors can affect health and reduce the effects of diseases.…”
Section: Introductionmentioning
confidence: 99%